Chapter 11 - Valorization of waste and by-products from food industries through the use of innovative technologies - Zhu, Zhenzhou; Gavahian, Mohsen; Barba, Francisco J.; Roselló-Soto, Elena; Bursać Kovačević, Danijela; Putnik, Predrag; Denoya, Gabriela Inés (Elsevier, 2020)
Food waste and by-products, which are normally regarded as not being valuable, have great potential for valuable compounds production. Valorization of these materials not only means more nutrients or bioactive compounds, but also addresses environmental issues caused by discarding these “waste” materials. This chapter discusses the nutritive and economic potential of food waste and by-products, as well as the application of innovative technologies (i.e., electrotechnologies, ultrasound, high hydrostatic pressure, nanotechnology, pressurized fluids) in food waste and by-products valorization. Such technologies improve the perspectives regarding waste utilization, paving the ways toward sustainable industrial development, which is one of the basic pillars for public health.